STUDI KASUS: ASUHAN KEPERAWATAN PASIEN PNEUMONIA DI RUMAH SAKIT HERMINA BEKAS - Musripah; Nadia Oktiffany Putri; Siti Haniifah Nurdin (JURNAL ILMIAH KEPERAWATAN ALTRUISTIK, 2023)
Pneumonia is an acute infectious disease in alveoli caused by microorganisms. Symptoms of pneumonia are coughing and shortness of breath. World deaths caused by pneumonia in 2019 reached 2.49 million people. The prevalence of pneumonia in Indonesia is increasing, in 2013 it was 4.0% and became 4.5% in 2018. The prevalence of pneumonia in West Java was 2.6%. According to medical record data in the general treatment room at Hermina Bekasi Hospital in December 2022-February 2023, the number of pneumonia patients recorded was 8.2% or 298 patients. The aim of this case study was to provide an overview of the nursing care implementation for pneumonia patients. The study used a descriptive method with a case study approach. This study was conducted in the general treatment room on the 4th floor of Hermina Bekasi Hospital. This study was conducted on March, 14th 2023 until March, 16th 2023. The subject in this case study was 1 patient with pneumonia. The findings showed that the patient was treated with several nursing problems, namely airway clearance, hyperthermia, risk of infection, and risk of nutritional deficit. After providing nursing care for each problem, 3 problems were resolved. One nursing problem that has not been resolved was the risk of infection because leukocyte levels did not yet show normal levels. The follow-up was that the patient will advise to undergo outpatient treatment. In conclusion, the findings highlight that important to emphasize airway management interventions to maintain and improve patient airway patency in pneumonia patients.